2018
DOI: 10.1080/0142159x.2018.1473562
|View full text |Cite
|
Sign up to set email alerts
|

What are the features of targeted or system-wide initiatives that affect diversity in health professions trainees? A BEME systematic review: BEME Guide No. 50

Abstract: Several intervention types may increase diversity. Limited applicant pools were a rate-limiting feature, suggesting efforts earlier in the continuum are needed to broaden applicant pools. There is a need to examine underlying cultural and external pressures that limit programs' acceptance of initiatives to increase diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 85 publications
0
26
0
Order By: Relevance
“…Furthermore, strategies to build diversity infrastructure should be supported by evidence, which is limited for the field of GC (Channaoui, Bui, et al, 2020). A 2018 review article (Simone et al, 2018) concluded that a multi-faceted approach may be more valuable rather than focusing on a single intervention. However, the most abundant evidence of success was among interventions targeting the admissions process, including the following key features: awarding points for underrepresented minority status; altered weighting of existing admissions criteria; and use of application assistance.…”
Section: Many Of the Experiences Reported By Participants In This Studymentioning
confidence: 99%
“…Furthermore, strategies to build diversity infrastructure should be supported by evidence, which is limited for the field of GC (Channaoui, Bui, et al, 2020). A 2018 review article (Simone et al, 2018) concluded that a multi-faceted approach may be more valuable rather than focusing on a single intervention. However, the most abundant evidence of success was among interventions targeting the admissions process, including the following key features: awarding points for underrepresented minority status; altered weighting of existing admissions criteria; and use of application assistance.…”
Section: Many Of the Experiences Reported By Participants In This Studymentioning
confidence: 99%
“…There is no reason to believe that this sorting system has optimized our workforce to meet societal demands or that it could not be improved upon. Holistic review processes reflect the capacity of schools and residencies to assess excellence across multiple domains and select candidates whose areas of focus, capabilities, approaches to learning, and values match those of the program and society [53][54][55].…”
Section: All Patients Need Excellent Physiciansmentioning
confidence: 99%
“…deficits and reduce discrimination. 16,17 Individual residency programs in multiple specialties, including family medicine, have reported initiatives to address diversity [18][19][20][21][22][23][24][25][26][27] that include antidiscrimination efforts, training on implicit bias, and holistic reviews for admissions. We assessed the national status of reported discrimination in educational and clinical environment and efforts to integrate training in diversity and inclusion training within programs.…”
Section: Resultsmentioning
confidence: 99%